2010
DOI: 10.4103/0970-4388.66744
|View full text |Cite
|
Sign up to set email alerts
|

Natural prevalence of antibody titers to Glucostltransferase of Streptococcus mutans in serum in high and low caries active children

Abstract: In this investigation, serum immunoglobulin G (IgG) and immunoglobulin A (IgA) titers, as well as total immunoglobulin concentration (IgG + IgA + IgM), were found to be raised with the increase in the number of dental caries. Only the total serum antibody titer in high dental caries (HDC) group was found to be significantly raised as compared to no dental carries (NDC) group. Although the IgG and IgA titers were raised in blood with the increased number of caries, the results were not statistically significant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…Raised serum IgG antibody titers to S. mutans are found in subjects with carious lesions ( Figure 5) compared with those without (Challacombe et al, 1984;Kirtaniya et al, 2010). This was confirmed in longitudinal studies and appears similar to that found in most infective diseases, in which a rise in antibodies following infection is commonly found.…”
Section: Immune Responses Following Dental Cariessupporting
confidence: 79%
“…Raised serum IgG antibody titers to S. mutans are found in subjects with carious lesions ( Figure 5) compared with those without (Challacombe et al, 1984;Kirtaniya et al, 2010). This was confirmed in longitudinal studies and appears similar to that found in most infective diseases, in which a rise in antibodies following infection is commonly found.…”
Section: Immune Responses Following Dental Cariessupporting
confidence: 79%
“…Bagherian et al [25] reported that the high concentration of salivary immunoglobulin in children with early childhood caries may be associated with an increased antigenic load, leading to high production of antibodies. According to a study by Kirtaniya et al [26], the increase in serum IgG, IgA and total antibody titer showed a direct correlation with the increase in number of carious lesions.…”
Section: Discussionmentioning
confidence: 94%